Evaluation of Settlement Space Patterns in Solok City with Remote Sensing - Siti Naila Tassa Ghuba Afti; Fitriana Syahar (Journal of Applied Geospatial Information, 2022)
Land use is the physical form of the earth's surface that is influenced by human activities. The increase in population results in changes in land use for settlements that tend to increase and are not controlled, so it is necessary to monitor the rate of these changes so that the balance of life and the environment can be maintained and in accordance with what has been regulated by the government in the regional spatial plan (RTRW). This study aims to identify changes in settlement area from 2010-2020 in Solok City and assess the suitability of land use for settlements with residential spatial patterns (RTRW) in 2012-2031 Solok City. This study uses remote sensing data in the form of spot images. The steps taken by the image interpretation approach with manual digitization methods and arcgis applications, accuracy sampling is done by random sampling with the confusion matrix accuracy test technique carried out to answer the goal. The results of the study found that the image accuracy was 91.66%. Then, the condition of settlements in Solok City continues to increase in area every year in the 2010-2020 period with a total of 353.8 Ha, where the largest area of ​​settlement changes is in Lubuk Sikarah District. In this study, it can be stated that the area of ​​settlement in 2020 is 306.50 Ha which is not in accordance with the area contained in the spatial pattern (RTRW) of Solok City